Enhancement of the Academic Performance of Polytechnic Students Through Timely and Effective Counseling - Mulla, Ansar Allauddin; Nalawade, Varsha; Jadhav, Hanmant (Journal of Social and Scientific Education, 2025)
This study investigates the core problem of inadequate academic performance and limited student engagement among polytechnic students, addressing how timely and effective Counseling can serve as a strategic intervention. Conducted at Rajarambapu Institute of Technology (RIT), the research involved Diploma-level students identified through academic records, mentor observations, and informal interactions based on academic, social, and emotional criteria. The study population included students from First, Second, and Third-Year diploma programs, with purposive sampling used to select those in need of support. Data was collected through mentoring reports, counseling documentation, academic performance records, and student feedback surveys. The analysis combined quantitative comparisons of pre- and post-counseling academic results with qualitative insights from student reflections. Findings show that personalized and group Counseling, when integrated with active learning strategies and developmental workshops, significantly enhance academic achievement, student confidence, and participation in college activities. This study underscores the value of embedding structured Counseling and mentoring practices within the academic system to support holistic student development. Future research should examine the long-term effects and scalability of such interventions across diverse educational contexts.